ANALISIS YURIDIS TERHADAP PENEGAKAN HUKUM TINDAK PIDANA KORUPSI TERHADAP PENENTUAN KERUGIAN KEUANGAN NEGARA (STUDI PUTUSAN NO.1596 K/PID.SUS/2013) - Erick Erick; Madiasa Ablisar; Sunarmi -; M. Ekaputra - (jurnal.unprimdn.ac.id, 2021)
Returning losses from the proceeds of corruption will make the perpetrator unable to enjoy the results of his actions. This can be done by seizing certain items obtained or produced in a criminal act as a criminal in carrying out the principle of the life of the nation and state. Basically, state losses occur if the achievements received by the state are less than the money paid by the state. The research method in this thesis is a normative legal research method, namely by conducting library research namely research conducted by examining library materials, especially laws and legal literature relating to problems. The source of data used in this thesis is in the form of prier legal material and or secondary legal material that has to do with qualitative problems, namely what is obtained from research in the field is studied in a comprehensive and comprehensive manner.